МАДАНИЯТЛАРАРО МУЛОҚОТ ВА ТАРЖИМА МУАММОЛАРИ (Scientific journal of the Fergana State University, 2023)
The article presents a comprehensive analysis of the unity of the form and content of translations and requirements for translation using the example of a number of works